Pengaruh Platform Penjualan Online (Khususnya Tik Tok Shop) Terhadap UMKM - Ragil Ayu Prasiska; Rahmawati, Ferida; Fikri, M. Khoirul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study examines the impact or influence of using the TikTok Shop platform on MSMEs in Indonesia, focusing on the use of the TikTok Shop platform in increasing product sales. The results highlight the shift in consumer behavior that is more likely to shop online, as well as the benefits provided by TikTok Shop for MSMEs that adopt it, such as increased sales and product visibility. However, challenges also arise for MSMEs that do not keep up with this digital trend, with the potential for a decline in sales in their offline markets. The recommendations involve digital training, online promotion, further study, and policy development that supports the digital transformation of MSMEs. To achieve a balance between online and offline sales, MSMEs can integrate online and offline strategies, provide loyalty programs, improve customer experience, conduct data analysis, diversify products and services, establish partnerships with e-commerce platforms, and conduct continuous monitoring and evaluation of their online and offline sales performance.